2021
DOI: 10.1177/20543581211056479
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Patients With ADPKD

Abstract: Purpose of review: Patients with autosomal dominant polycystic kidney disease (ADPKD) have kidney cysts and kidney enlargement decades before progressing to advanced chronic kidney disease (CKD), meaning patients live most of their adult life with a chronic medical condition. The coronavirus disease 2019 (COVID-19) pandemic has created common questions among patients with ADPKD. In this review, we discuss COVID-19 concerns centered around a patient with a common clinical vignette. Sources of information: We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…While data remain quite limited, there is no evidence to suggest ADPKD increases the likelihood of hospitalization, dialysis, or mortality over and above the risk conferred by the degree of CKD. Other study have not shown an increase in hospitalization, intensive care unit admission, intubation, or mortality following COVID-19 infection in patients with ADPKD compared with patients with other cystic kidney or cystic liver diseases [ 1 , 4 , 5 ]. While both conditions involve kidney dysfunction, the etiology, progression, and management strategies differ significantly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While data remain quite limited, there is no evidence to suggest ADPKD increases the likelihood of hospitalization, dialysis, or mortality over and above the risk conferred by the degree of CKD. Other study have not shown an increase in hospitalization, intensive care unit admission, intubation, or mortality following COVID-19 infection in patients with ADPKD compared with patients with other cystic kidney or cystic liver diseases [ 1 , 4 , 5 ]. While both conditions involve kidney dysfunction, the etiology, progression, and management strategies differ significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the systemic effects of COVID-19, such as hypoxia and coagulopathy, may further compromise kidney health in ADPKD patients [ 5 ]. Moreover, it is known that SARS-CoV-2 virus utilizes ACE2 receptors on cell membranes to determine the damage, and it is well-documented that the RAAS is more active in ADPKD patients [ 1 ]. The use of ACEIs and ARBs in the context of COVID-19 has been a subject of significant debate and research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining individual omics data with demographical/ethnic data and prior health conditions (patients' phenomes) allowed for the identification of genes and molecular pathways involved in COVID-19 hospitalization cases [142,149]. Strong associations were identified between multiome biomarkers and individuals' pre-existing conditions, such as kidney disease, ischemic heart disease, cerebrovascular disease, and hypertension [150,151].…”
Section: Cross-ome Bioinformatic Data Mining and Analyticsmentioning
confidence: 99%